MANAJEMEN ADMINISTRASI PENDIDIKAN DALAM MENINGKATKAN MUTU AKREDITASI DI UPTD SDN 1 CITAMIANG KECAMATAN MANIIS - Dewi, Ratna; Nurlaeli, Leli; Latifah, Aida; Normayunita, Rizki; suwandari, Lilis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of educational administration management in improving accreditation quality at SDN 1 Citamiang, Maniis District, Purwakarta Regency. Using a descriptive qualitative approach, this research involved the principal, teachers, school operator, and the accreditation team as informants. Data were collected through observation, interviews, and documentation, and analyzed interactively through data reduction, presentation, and conclusion drawing. The results show that the management of educational administration at SDN 1 Citamiang has been carried out based on four management functions: planning, organizing, actuating, and controlling, but has not been fully optimal. In the planning aspect, the school has developed work plans systematically but has not maximized the use of evaluation results as a basis for planning. In organizing, task distribution is still unclear and not proportional, causing a workload imbalance, especially among teachers. In the actuating aspect, program implementation is hindered by a lack of understanding of accreditation instruments, limited resources, and minimal use of information technology. Meanwhile, the controlling aspect is still incidental and not conducted routinely and systematically. Overall, the study concludes that administrative management has a strong foundation but needs significant improvements in each function to support continuous improvement in accreditation quality. Keywords: educational administration, accreditation, management, planning, evaluation